The composition of cell‐based therapies obtained from point‐of‐care devices/systems which mechanically dissociate lipoaspirate: a scoping review of the literature - Perry Liu; Binay Gurung; Irrum Afzal; Matteo Santin; David H. Sochart; Richard E. Field; Deiary F. Kader; Vipin Asopa (Journal of Experimental Orthopaedics)
Abstract Purpose Cell‐based therapies using lipoaspirate are gaining popularity in orthopaedics due to their hypothesised regenerative potential. Several ‘point‐of‐care’ lipoaspirate‐processing devices/systems have become available to isolate cells for therapeutic use, with published evidence reporting their clinical relevance. However, few studies have analysed the composition of their ‘minimally‐manipulated’ cellular products in parallel, information that is vital to understand the mechanisms by which these therapies may be efficacious. This scoping review aimed to identify devices/systems using mechanical‐only processing of lipoaspirate, the constituents of their cell‐based therapies and where available, clinical outcomes. Methods PRISMA extension for scoping reviews guidelines were followed. MEDLINE, Embase and PubMed databases were systematically searched to identify relevant articles until 21st April 2022. Information relating to cellular composition and clinical outcomes for devices/systems was extracted. Further information was also obtained by individually searching the devices/systems in the PubMed database, Google search engine and contacting manufacturers. Results 2895 studies were screened and a total of 15 articles (11 = Level 5 evidence) fulfilled the inclusion criteria. 13 unique devices/systems were identified from included studies. All the studies reported cell concentration (cell number regardless of phenotype per millilitre of lipoaspirate) for their devices/systems (range 0.005–21 × 106). Ten reported cell viability (the measure of live cells‐ range 60–98%), 11 performed immuno‐phenotypic analysis of the cell‐subtypes and four investigated clinical outcomes of their cellular products. Only two studies reported all four of these parameters. Conclusion When focussing on cell concentration, cell viability and MSC immuno‐phenotypic analysis alone, the most effective manual devices/systems were ones using filtration and cutting/mincing. However, it was unclear whether high performance in these categories would translate to improved clinical outcomes. Due to the lack of standardisation and heterogeneity of the data, it was also not possible to draw any reliable conclusions and determine the role of these devices/systems in clinical practice at present. Level of Evidence Level V Therapeutic.